Validation of the Rosenberg self-esteem scale in students of the Adventist University of Bolivia - Molina Calle, Pablo (2024)
The objective of this study was to determine the degree of validity of the Rosenberg Self-Esteem Scale in students of the Adventist University of Bolivia in 2023. This study is instrumental, with a quantitative approach, with a non-experimental cross-sectional design. descriptive. The primary intention is to describe the characteristics of the scale, indicating its particularities and manifestations. Likewise, the normative values of the scale are established in the context of the study population, it is based on studies previously carried out at an international level. The data collection procedure was through the technique of a questionnaire instrument of the Rosenberg Self-Esteem Scale with ten items with a positive dimension and a negative dimension. The study population was made up of a non-probabilistic convenience sample of 316 participants (N=1476). According to the results obtained in this study, the distribution and magnitude of the level of self-esteem in university students is evident, that is, it is determined that the Rosenberg Self-Esteem Scale reached the degree of validity through the Alpha coefficient. Cronbach’s scale with the value of 0.881, this means as a conclusion that the Rosenberg Self-Esteem Scale is valid for its administration in the context of the study population.